Aβ1–40 Oligomers Trigger Neutrophil Extracellular Trap Formation through TLR4- and NADPH Oxidase-Dependent Pathways in Age-Related Macular Degeneration - Chen, Jinquan; Zhao, Long; Ding, Xuanheng; Wen, Yan; Wang, Lingda; Shu, Qinxin; Xie, Wenxi; Liu, Yanyao; Peng, H. (Oxidative medicine and cellular longevity, 2022)
Neutrophils participate in the advancement of the human innate immune system and respond to perceived endogenous and exogenous threats. As a response mechanism, neutrophil extracellular traps (NETs) form near pathogens and surrounding tissues during an immune response. Drusen is an important marker of Age-Related Macular Degeneration (AMD) and plays an important role in the course of AMD. Aβ1-40 is the main component of drusen. However, the relationship between NETs and AMD or Aβ1-40 is unclear. Here, we found elevated levels of NETs in the serum of AMD patients and elevated levels in the serum of mouse models. We also observed the accumulation of neutrophils in the mouse retina. In addition, the production of NETs was inhibited by PAD4 inhibitors, which can alleviate chronic inflammation. Moreover, we confirmed that Aβ1-40 can induce NETs formation via the Toll-like receptor 4 (TLR4) and neutrophil NADPH oxidase (NOX) pathways. Our study confirmed that the formation of NETs is induced by Aβ1–40, and the results suggest that NETs may play a vital role in AMD pathogenesis.